Metronidazole-loaded gold nanoparticles in natural rubber latex as a potential wound dressing - Borges, Felipe Azevedo [UNESP]; de Camargo Drago, Bruno [UNESP]; Baggio, Luís Otávio [UNESP]; de Barros, Natan Roberto; Sant'Ana Pegorin Brasil, Giovana [UNESP]; Scontri, Mateus [UNESP]; Mussagy, Cassamo Ussemane; da Silva Ribeiro, Matheus Cícero; Milori, Débora Marcondes Bastos Pereira; de Morais, Carla Pereira; Marangoni, Bruno Spolon; Nicolodelli, Gustavo; et al. (Elsevier, 2022)
Gold nanoparticles (AuNPs) have shown interesting properties and specific biofunctions, providing benefits and new opportunities for controlled release systems. In this research, we demonstrated the use of natural rubber latex (NRL) from Hevea brasiliensis as a carrier of AuNPs and the antibiotic metronidazole (MET). We prepared AuNP-MET-NRL and characterized by physicochemical, biological and in vitro release assays. The effect of AuNPs on MET release was evaluated using UV–Vis and Laser-Induced Breakdown Spectroscopy (LIBS) techniques. AuNPs synthesized by Turkevich and Frens method resulted in a spherical shape with diameters of 34.8 ± 5.5 nm. We verified that there was no emergence or disappearance of new vibrational bands. Qualitatively and quantitatively, we showed that the MET crystals dispersed throughout the NRL. The Young's modulus and elongation values at dressing rupture were in the range appropriate for human skin application. 64.70% of the AuNP-MET complex was released within 100 h, exhibiting a second-order exponential release profile. The LIBS technique allowed monitoring of the AuNP release, indicating the Au emission peak reduction at 267.57 nm over time. Moreover, the dressing displayed an excellent hemocompatibility and fibroblast cell viability. These results demonstrated that the AuNP-MET-NRL wound dressing is a promising approach for dermal applications.
Keywords: Gold nanoparticles; LIBS; Sustained release